Immune responses, upper respiratory illness symptoms, and load changes in young athletes during the preparatory period of the training periodization - Brunelli, D. T.; Borin, J. P.; Rodrigues, A.; Bonganha, V.; Prestes, J.; Montagner, P. C.; Cavaglieri, C. R. (Open Access Journal of Sports Medicine, 2012)
Objective: The aim of this study was to investigate the immunological responses and the association between variation in exercise load and self-reported occurrence of upper respiratory illness (URI) symptoms in young basketball athletes. Materials and methods: The sample was composed of twelve young male athletes aged 12.7 ± 0.6 years, with a height of 170 ± 10 cm, body mass of 57.6 ± 12.6 kg, and fat-free mass of 18.7 ± 5.9%. Daily training and occurrences of URI symptoms were recorded. Blood samples were collected at baseline (M1) and after 8 weeks (M2) of the preparatory period of periodization training to measure total and differential leukocyte counts, serum interleukin-6 (IL-6), and tumor necrosis factor-a (TNF-a). Results: There was a significant decrease in monocytes at M2 compared to M1 (P = 0.004). There were no significant alterations in total leukocytes (P = 0.07), neutrophils (P = 0.07), or lymphocytes (P = 0.09). No significant changes in plasma concentrations of TNF-a (P = 0.30) or IL-6 (P = 0.90) were found. The weekly load from week 6 was higher when compared with weeks 1, 2, 4, and 8 (P < 0.05), and week 8 was the lowest when compared with week 5 (P < 0.05). Self-reported URI incidences were highest at weeks 1 and 2. Conclusion: Variations in weekly training load during the preparatory period were not correlated with changes in self-reported occurrence of URI incidences, suggesting that young athletes may have an attenuated response to exercise-induced perturbations to the immune system.